Clopidogrel resistance and its relevance: Current concepts - Akshyaya Pradhan; Monika Bhandari; Pravesh Vishwakarma; Rishi Sethi (Journal of Family Medicine and Primary Care, 2024)
Clopidogrel is the most widely used P2Y12 receptor inhibitor (P2Y12i) as a part of dual antiplatelet therapy along with aspirin. Clopidogrel is a pro-drug and is metabolized to its active metabolite by the hepatic enzyme cytochrome P4502C19 (CYP2C19). This active metabolite is responsible for the antiplatelet action of clopidogrel. Recent studies have demonstrated that single nucleotide polymorphisms in the CYP2C19 gene, including CYP2C19*2,*3,*4, and *5 alleles, result in reduced production of the active metabolite of clopidogrel, and hence reduced inhibition of platelet aggregation. This in turn enhances the incidence of stent thrombosis and recurrent cardiovascular (CV) events. We report a case of coronary stent thrombosis due to clopidogrel resistance proven by CYP2C19 genotyping. We then review the literature on clopidogrel resistance and its impact on CV outcomes. Subsequently, we discuss the methods of diagnosis of resistance, evidence from clinical trials for tailoring clopidogrel therapy, the role of potent P2Y12 inhibitors, the current guidelines, and future directions.